2019
DOI: 10.2298/zipi1901238s
|View full text |Cite
|
Sign up to set email alerts
|

Towards creative transformational leadership in higher education: Challenges and opportunities

Abstract: Месни универзитет на мађарском језику, Комарно, Мађарска Апстракт. Циљ овог рада је да се дефинише шта креативно трансформационо лидерство значи у контексту високог образовања и да се открију неки од изазова и неке могућности које има лидер у образовању у институцијама са интернационалним карактером које се такмиче на глобалном тржишту. Аутори су истраживали и раније студије које су указале на чињеницу да је "трансформационо лидерство" најефикаснији модел лидерства, посебно у пословном контексту, док се многи … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Just one study related this dimension to a leadership style and an aspect of digital transformation. Smith and Vass (2019) sought to define creative transformational leadership in the context of higher education's internationalisation and competition in a global market. For the authors, this is the ideal style, as it allows increased trust and loyalty, creativity and innovation, development of individual potential and transformation of the organisational culture.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Just one study related this dimension to a leadership style and an aspect of digital transformation. Smith and Vass (2019) sought to define creative transformational leadership in the context of higher education's internationalisation and competition in a global market. For the authors, this is the ideal style, as it allows increased trust and loyalty, creativity and innovation, development of individual potential and transformation of the organisational culture.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that strong leadership is necessary to reduce the barriers to the adoption of new technologies in HEIs (Birch and Burnett, 2009), the studies surveyed confirm the important, positive role of transformational leadership in influencing students' effective use of online education systems (Aldholay et al. , 2019), and in creating favourable conditions for HEIs' better adaptation to the social and technological environment in continuous change (Smith and Vass, 2019). Structured leadership is also considered as a predictor of the implementation of improved learning schemes through the introduction of new technologies (Zhu, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need for more diversity in studies on transformational leadership and organizational change context is a noteworthy lacuna in the current study landscape. The majority of researchers' conclusions are based on primary sources from the West or places developed industrially, and the local background of these places is not being studied much (Smith & Vass, 2019). The mistake demonstrated that there is a need for research that explains how leadership transformational principles differ and are used in different cultures, especially in developing economies where leadership dynamics are diverse.…”
Section: Research Gapmentioning
confidence: 99%
“…The distinct culture, economy, and diversity of workers and organizations in Baluchistan make this region a very locus for engaging transformational leadership in the context of organizational change. According to Smith and Vass (2019), the region's characteristics demand the application of adaptive leadership approaches for the implementation of change initiatives to be successful. The practical implications of this research for MNCs planning to expand into various regions of Baluchistan are significant.…”
Section: Introductionmentioning
confidence: 99%